The law applicable in the form of an arbitration agreement - Belahouan, Hocine (Journal of Human Sciences, 2020)
the continuous development of international trade contracts made it distinct from other contracts. Applicable to each, a similar distinction in this regard between the subject matter and the form of the arbitration agreement, as a contract applicable to the provisions applicable to the international contract conflict of law However, this did not prevent the arbitration agreement from being unique in regard to the law applicable in its form with provisions that are distinct from other contracts because of its special nature Writing is the most important aspect of the form required by the arbitration agreement. The arbitration agreement is necessary to prove the agreement or to prove its convening, as some of them went to enforce the law governing the subject in the form necessary to convene, while another side stuck to the implementation of the objective methodology in this regard, and there are those who called for the application of the conflict method.